'Solemn and just demands': Seeking apologies in the international arena. Issue 4 (28th October 2020) - Adams, Tracy; Kampf, Zohar
Abstract: Demands for apology are a prominent rhetorical means for pointing out transgressions in contemporary world politics. They transform 'seen but unnoticed' conduct into 'seen and noticed' transgression and attach a price tag to the restoration of damaged relations. Nevertheless, compared to the widely discussed practice of apologising, demands for apologies have received scant scholarly attention. In this article we adopt an actor-oriented perspective in order to situate the speech act of demanding an apology within the delicate management of interstate relations. In-depth content analysis of 57 cases of demands made by various state actors in a variety of diplomatic contexts between 1999 and 2019 let us delineate the discursive construction of transgressions, the normative scripts that inform acts of demands, the types of sought-after remedies, and their discursive consequences. We conclude by discussing the normative diplomatic scripts that guide demands for apology and how these speech acts reconfigure power relations in international politics.